2017
DOI: 10.1016/j.jpba.2017.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of the traditional Chinese medicine formulation Yu Ping Feng San for the identification of constituents relevant for effects on expression of TNF-α, IFN-γ, IL-1β and IL-4 in U937 cells

Abstract: Yu Ping Feng San (YPFS) is a classical TCM formulation which has been traditionally used for treatment of immune system related diseases such as chronic bronchitis, allergic rhinitis and asthma. The formula is a mixture of Radix Saposhnikoviae (Fangfeng), Radix Astragali (Huangqi), and Rhizoma Atractylodis macrocephalae (Baizhu). TLC- and LC-DAD-ESI-MS/MS methods have been developed for the analysis of the metabolic profiles of the single herbs and of the formula. Decoctions and ASE extracts were analyzed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…OPLS-DA has an advantage over an unsupervised PCA method in that it separates the predictive variation from the orthogonal variation and can be studied and interpreted separately (Nikles et al, 2017). OPLS-DA has an advantage over an unsupervised PCA method in that it separates the predictive variation from the orthogonal variation and can be studied and interpreted separately (Nikles et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OPLS-DA has an advantage over an unsupervised PCA method in that it separates the predictive variation from the orthogonal variation and can be studied and interpreted separately (Nikles et al, 2017). OPLS-DA has an advantage over an unsupervised PCA method in that it separates the predictive variation from the orthogonal variation and can be studied and interpreted separately (Nikles et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the metabolites between the VC group and the sample groups and the control group and the model group are shown as coefficient of variation plots. OPLS-DA has an advantage over an unsupervised PCA method in that it separates the predictive variation from the orthogonal variation and can be studied and interpreted separately (Nikles et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ese results showed that the tumor microenvironment of HCC was 2-dominanted immunosuppression. YPF, a classical TCM formulation, has been traditionally used for treatment of immune systemrelated diseases such as chronic bronchitis, allergic rhinitis, and asthma [36]. A previous study has demonstrated that YPF efficiently inhibited 2 cytokines [15].…”
Section: Downregulatedmentioning
confidence: 99%